A Study on the Construction Model of Ancient Vietnamese Capital Cities - Yao, Congcong; Wang, Yan (International Planning History Society Proceedings, 2024)
China’s urban planning theories originated from the ‘harmonious relationship between humans and nature’ perspective of ancient environmental culture, which was disseminated through the process of ‘Mutual Understanding of Civilisations’. Vietnam is geographically adjacent to China, and has the closest relationship with China in the Southeast Asian region. Numerous cultural artefacts and symbolic elements dating back to the Stone Age have demonstrated the cultural origins of the two countries. The northern region of Vietnam has been under the control of the Chinese Feudal Dynasties from the third century B.C.E. until the early tenth century. After gaining independence, Vietnam continued to have a suzerain-vassal connection with China for about nine centuries. Vietnam is a significant research subject in the "Han Cultural Circle" because of the aforementioned variables that have contributed to a high degree of cultural resemblance between China and Vietnam. In order to determine the genetic relationship between the original mode and localised innovation from the perspective of urban planning history, this study will compare and contrast the construction models of ancient Vietnamese and Chinese capital cities. Additionally, it will show how Chinese urban planning theories have influenced Southeast Asian urban construction activities, either directly or indirectly.